Domestic Undergraduate Students’ Perceptions of Internationalisation at Home in Thailand: Conflicts of Recognition Surrounding International EMI Programmes - Taylor, Pimsiri; Tubpun, Tida; Burford, James (rEFLections, 2022)
In Southeast Asian countries such as Thailand, higher education internationalisation agendas have increasingly shifted from studying abroad to offering ‘international’ English-medium instruction (EMI) programmes at home. This qualitative study explores the perceptions of seventeen domestic undergraduate students in the disciplines of Law and Business Studies regarding internationalisation at home (IaH) in Thailand. Findings from the focus group interviews revealed that domestic students positioned international EMI programmes as somewhere in the middle between studying abroad and standard domestic programmes. Moreover, these students associated international EMI programmes in Thai higher education with significant EMI, greater inbound mobility, and different teaching approaches. However, the in-between status of international EMI programmes can lead to conflicts of recognition as to whether such programmes are ‘international enough’. This article offers a close-up investigation of complex meanings that circulate around IaH in the Thai context, contributing to a broader picture of the varied enactments of IaH across higher education institutions.